2020
DOI: 10.1002/cbic.202000014
|View full text |Cite
|
Sign up to set email alerts
|

2′/3′ Regioselectivity of Enzyme‐Free Copying of RNA Detected by NMR

Abstract: The RNA‐templated extension of oligoribonucleotides by nucleotides produces either a 3′,5′ or a 2′,5′‐phosphodiester. Nature controls the regioselectivity during RNA chain growth with polymerases, but enzyme‐free versions of genetic copying have modest specificity. Thus far, enzymatic degradation of products, combined with chromatography or electrophoresis, has been the preferred mode of detecting 2′,5′‐diesters produced in enzyme‐free reactions. This approach hinges on the substrate specificity of nucleases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…The linkage type in polymerisation was also confirmed by 31 P NMR (Figure 1d) and the peaks were assigned based on the literature values. 24,25 Copolymerisation of cNMP We tested the polymerisation tendencies of cAMP, cUMP and cCMP under the same heat-drying conditions and found that these monomers did not polymerise to the same lengths and concentrations as cGMP. Figure 2a shows the polymerisation trend decreases in the order cGMP> cUMP> cAMP > cCMP.…”
Section: Reduced Concentration Of N-mers >3 Is Observed For 80 °C Pos...mentioning
confidence: 99%
“…The linkage type in polymerisation was also confirmed by 31 P NMR (Figure 1d) and the peaks were assigned based on the literature values. 24,25 Copolymerisation of cNMP We tested the polymerisation tendencies of cAMP, cUMP and cCMP under the same heat-drying conditions and found that these monomers did not polymerise to the same lengths and concentrations as cGMP. Figure 2a shows the polymerisation trend decreases in the order cGMP> cUMP> cAMP > cCMP.…”
Section: Reduced Concentration Of N-mers >3 Is Observed For 80 °C Pos...mentioning
confidence: 99%
“…in a 0.5 m m 3‐(N‐morpholino)propanesulfonic acid (MOPS) buffer, containing 1‐ethylimidazole (0.15 m m ) and MgCl 2 (0.08 m m ) (pH 7.5). These reaction conditions were derived from Richert and co‐workers and are referred to as “condensation buffer.” [46] As shown in Figure 3B, the 31 P NMR signal (∼3.8 ppm) of X 15 MP gradually decreased and vanished after 3 h. Meanwhile, a new signal around ‐11.0 ppm appeared and accumulated, indicating the formation of pyrophosphate X 15 ppX 15 , based on the characteristic chemical shift [47,67] . While non‐substituted adenosine monophosphates also form some phosphodiesters, [47,67] we did not observe this for X 15 MP .…”
Section: Resultsmentioning
confidence: 73%
“…The linkage type in the polymerisation was also confirmed by 31 P NMR (Figure 1d) and the peaks were assigned based on the literature values. [32,33] Figure 1a and 1b compare the effect of pH on the lengths and concentrations of the n-mers formed by drying with K + (Cl -) and imidazole respectively. We determined the optimal reaction temperature to be 40 °C (S5, S8b).…”
Section: Polymerisation Of Cgmpmentioning
confidence: 99%